LEGAL PERSPECTIVES ON FREE ASSOCIATION AMONG TEENAGERS - Mhd Alfa Ridho Fahlevi (Academic Solution Publisher, 2024)
Free association among teenagers has become one of the social issues that attracts attention in various fields, including law. Free association refers to social interactions that are not bound by clear norms or boundaries, which often involve risky behavior, such as drug abuse, premarital sex, and the spread of sexually transmitted diseases. In this context, the law has an important role in providing restrictions, protection, and sanctions against behaviors that can endanger the health and morality of teenagers. This study aims to examine the legal perspective on free association among teenagers, with a focus on existing regulations in Indonesia and how the law can play a role in preventing the negative impacts of free association. Through a normative approach, this study analyzes laws and regulations that regulate adolescent behavior, such as the Child Protection Law, as well as government policies related to preventing free association. The results of the study show that although the law has provided a clear basis for protecting teenagers, the implementation of regulations that are still less than optimal and the lack of effective supervision are major challenges. Therefore, it is important to improve legal education for teenagers and strengthen the role of society in supervising and guiding them to avoid the negative influences of free association